Constructing Islamic economic principles to control consumptive lifestyles in the digital era - Umi Nurhayati; Nida Qahtan Fattah (Novera: Journal of Economics and Business, 2026)
Consumptive lifestyles are increasingly shaped by digital consumption, self-reward, trends, and status-oriented purchases, while previous studies tend to separate discussions of consumerism from Islamic consumption principles. This study aims to construct Islamic economic principles as boundaries and orientations for controlling consumptive lifestyles. A qualitative library research approach was employed by synthesizing literature on contemporary consumer behavior and Islamic economics, supported by an illustrative calculation of the Average Propensity to Consume (APC). The findings show that consumerism is determined not merely by the type or amount of expenditure, but by consumption motives, proportionality, benefit, wastefulness, and financial consequences. Five principles—maslahah, wasatiyyah, isrāf, tabdhīr, and ḥifẓ al-māl—are constructed to distinguish rational, moderate, consumptive, and excessive consumption. The study contributes a conceptual construction that integrates economic indicators with Islamic normative principles. Abstrak Gaya hidup konsumtif semakin berkembang melalui konsumsi digital, self-reward, tren, dan pembelian berbasis status, sementara kajian terdahulu cenderung memisahkan pembahasan perilaku konsumtif dari prinsip konsumsi Islam. Penelitian ini bertujuan mengonstruksikan prinsip ekonomi Islam sebagai batas dan orientasi untuk mengendalikan gaya hidup konsumtif. Penelitian menggunakan pendekatan kualitatif dengan desain studi kepustakaan melalui sintesis literatur mengenai perilaku konsumsi modern dan ekonomi Islam, yang didukung oleh perhitungan ilustratif Average Propensity to Consume (APC). Hasil penelitian menunjukkan bahwa konsumtivisme tidak ditentukan semata-mata oleh jenis barang atau besarnya pengeluaran, tetapi oleh motif konsumsi, proporsi, kemanfaatan, pemborosan, dan konsekuensi finansial. Lima prinsip, yaitu maslahah, wasatiyyah, isrāf, tabdhīr, dan ḥifẓ al-māl, dikonstruksikan untuk membedakan konsumsi yang rasional, moderat, konsumtif, dan berlebihan. Kontribusi penelitian terletak pada konstruksi konseptual yang mengintegrasikan indikator ekonomi dengan prinsip normatif Islam.